Ekonomi Islam dalam Sistem Ekonomi Indonesia (Studi tentang Prinsip-prinsip Ekonomi Islam dalam KHES dan Implementasinya terhadap Ekonomi Nasional) - Yanti, Illy; Rafidah, Rafidah (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2009)
Economic crisis which knock over world in this time, is factor from mistake of itself human being, running economic system capitalist, this system only giving wide of opportunity to big investors, whereas small investors will be pulled over. Differ the things of with economic system of Islam applying the infinite system, justice, prohibition order obligation and lap pay forreligious obligatory (zakat). This matter make economic growth and growth of Islam go forward by significant. Therefore need the existence of Islam economic principle implementation in national economic system. One of the way of by applying sharing holder system (profit-sharing).